2013
DOI: 10.1103/physrevlett.110.010502
|View full text |Cite
|
Sign up to set email alerts
|

Surface Code Threshold in the Presence of Correlated Errors

Abstract: We study the fidelity of the surface code in the presence of correlated errors induced by the coupling of physical qubits to a bosonic environment. By mapping the time evolution of the system after one quantum error correction cycle onto a statistical spin model, we show that the existence of an error threshold is related to the appearance of an order-disorder phase transition in the statistical model in the thermodynamic limit. This allows us to relate the error threshold to bath parameters and to the spatial… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 17 publications
(24 reference statements)
2
55
1
Order By: Relevance
“…The standard approach for mitigating these errros is to use a faulttolerant error-correction protocol, which enables arbitrarily large computations as long as the strength of the errors are below a threshold value [1-5] and are not overly correlated in space or time [6][7][8][9][10]. The fault-tolerant error threshold is a measure of the robustness of a quantum computing platform and an estimate of its value is one of the most important tasks for practical quantum computer design.…”
Section: Pauli Twirling Approximationmentioning
confidence: 99%
“…The standard approach for mitigating these errros is to use a faulttolerant error-correction protocol, which enables arbitrarily large computations as long as the strength of the errors are below a threshold value [1-5] and are not overly correlated in space or time [6][7][8][9][10]. The fault-tolerant error threshold is a measure of the robustness of a quantum computing platform and an estimate of its value is one of the most important tasks for practical quantum computer design.…”
Section: Pauli Twirling Approximationmentioning
confidence: 99%
“…In a recent paper [20], two of us showed that the time evolution of the surface code in the presence of a common bosonic bath can be mapped onto a statistical spin model. This mapping allows for the computation of the surface code fidelity much in the same way that one computes the partition function and expectation values in a spin model.…”
Section: Introductionmentioning
confidence: 99%
“…Following Refs. [11,12], we consider in the following the perfect measurement case p m = 0 for definiteness and simplicity. Generalization to the more realistic case of p m > 0 is straightforward; it merely corresponds to replacing p c (orp c , see below) by a lower value.…”
Section: Problem and Overviewmentioning
confidence: 99%
“…We have focused our discussion on the specific combination (D = 2, r = 0) investigated in Ref. [11], which corresponds to an Ohmic bath. This combination is of particular interest since it is the only one for which the maximal QEC time vanishes (very slowly) in the thermodynamic limit.…”
Section: Code Sizementioning
confidence: 99%
See 1 more Smart Citation